Overexpressing Kallistatin Aggravates Experimental Autoimmune Uveitis Through Promoting Th17 Differentiation - Chen, Nu; Chen, Shuang; Zhang, Zhihui; Cui, Xuexue; Wu, Lingzi; Guo, Kailei; Shao, Hui; Ma, Jian-Xing; Zhang, Xiaomin (Frontiers in Immunology, 2021)
Kallistatin or kallikrein-binding protein (KBP) has been reported to regulate angiogenesis, inflammation and tumor progression. Autoimmune uveitis is a common, sight-threatening inflammatory intraocular disease. However, the roles of kallistatin in autoimmunity and autoreactive T cells are poorly investigated. Compared to non-uveitis controls, we found that plasma levels of kallistatin were significantly upregulated in patients with Vogt-Koyanagi-Harada (VKH) disease, one of the non-infectious uveitis. Using an experimental autoimmune uveitis (EAU) model induced by human interphotoreceptor retinoid-binding protein peptide 651-670 (hIRBP651-670), we examined the effects of kallistatin on the pathogenesis of autoimmune diseases. Compared to wild type (WT) mice, kallistatin transgenic (KS) mice developed severe uveitis with dominant Th17 infiltrates in the eye. In addition, the proliferative antigen-specific T cells isolated from KS EAU mice produced increased levels of IL-17A, but not IFN-γ or IL-10 cytokines. Moreover, splenic CD4+ T cells from naïve KS mice expressed higher levels of Il17a mRNA compared to WT naïve mice. Under Th17 polarization conditions, KS mice exhibited enhanced differentiation of naïve CD4+ T cells into Th17 cells compared to WT controls. Together, our results indicate that kallistatin promotes Th17 differentiation and is a key regulator of aggravating autoinflammation in EAU. Targeting kallistatin might be a potential to treat autoimmune disease.